2020
DOI: 10.3390/foods9060810
|View full text |Cite
|
Sign up to set email alerts
|

Does High Voltage Electrical Discharge Treatment Induce Changes in Tannin and Fiber Properties of Cocoa Shell?

Abstract: Cocoa shell is a by-product of the chocolate industry that is rich in dietary fiber and bioactive components. In this research, the influence of high voltage electric discharge (HVED) treatment on chemical and physical characteristics of the cocoa shell, i.e., the effects of applied time and frequencies on grinding ability, water binding capacity (WBC), dietary fibers and tannin content was investigated. HVED had a significant influence on the chemical and physical properties of cocoa shell, all of which could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…While the The results also show that the dark and milk chocolate samples with HVED-treated cocoa shells had larger particles than the chocolates with untreated cocoa shells. This is in accordance with our previous research [13], where we showed that cocoa shells treated with HVED were harder to grind. According to Konar et al [22], particle size distribution inversely affects the hardness of chocolate because of the particle-particle interactions.…”
Section: Particle Size Distributionsupporting
confidence: 94%
See 1 more Smart Citation
“…While the The results also show that the dark and milk chocolate samples with HVED-treated cocoa shells had larger particles than the chocolates with untreated cocoa shells. This is in accordance with our previous research [13], where we showed that cocoa shells treated with HVED were harder to grind. According to Konar et al [22], particle size distribution inversely affects the hardness of chocolate because of the particle-particle interactions.…”
Section: Particle Size Distributionsupporting
confidence: 94%
“…In addition, chocolates with untreated cocoa shells had lower viscosities than those with HVED-treated shells. In our previous study, it was shown that treated cocoa shells had a higher oil-binding capacity than untreated ones [13]. Bolenz et al [14] stated that wheat fibers and cellulose can absorb oil, which leads to a reduced continuous fat phase.…”
Section: Rheological Propertiesmentioning
confidence: 94%
“…Another component influencing polyphenol behavior in food systems is fiber. In our previous researches we treated cocoa shell with HVED and explored its influence on polyphenols [ 25 ] and fiber [ 26 ]. HVED reduced contents of all analyzed polyphenolic components and increased content of insoluble fiber, which was reflected in properties of chocolates in this research.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to fiber content, porosity and surface properties of fiber, as well as molecular weight of polyphenols and polyphenol-protein complexes influence these interactions [ 19 ]. After HVED treatment, both oil- and water-binding capacities of cocoa shell increased [ 26 ], indicating that HVED could result in a more porous structure of fiber. The pores could entrap polyphenols not only from cocoa shell, but from cocoa mass as well, making them inaccessible for extraction and determination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation